A methodology for strain-based fatigue damage prediction by combining finite element modelling with vibration measurements. (March 2021) - Lagerblad, Ulrika; Wentzel, Henrik; Kulachenko, Artem
Highlights: A novel methodology for fatigue damage prediction based on strain field estimates. Strain fields estimated with a fixed-lag Kalman smoother. Demonstrated with a full-scale laboratory experiment of a vehicle component. Good correlation between vibration fatigue life rig test and predicted damage. Abstract: The possibility of predicting the fatigue life of vehicle components based on sparse in-service vibration measurements enables an optimization of the maintenance and utilization of a vehicle fleet. This paper presents a novel methodology for fatigue damage prediction based on strain fields estimated from sparse vibration measurements on a dynamic structure together with a finite element model. The strain is estimated with a fixed-lag Kalman smoother, which is based on a state-space model derived from a modal description of the finite element model. The methodology is demonstrated with a full-scale laboratory experiment of a vehicle component subjected to road- induced vibrations where both strains and accelerations were measured. Fatigue damage is computed from the estimated strains, and verification of the accuracy of the predicted damage showed good results. The proposed methodology was then followed when the outcome of a full-scale vibration fatigue rig test of the component was predicted. The computed damage predicted the same failure locations as the ones which occurred during the rig test. The good correlation between the numerically computed damage and the outcome of the fatigue rig test indicates that the methodology presented in this paper has a high potential in predicting fatigue damage.